Feasibility and acceptability of “Cuida tu Ánimo” (Take Care of Your Mood): an internet-based program for prevention and early intervention of adolescent depression in Chile and Colombia - Martínez, Vania; Espinosa-Duque, Daniel; Jiménez-Molina, Álvaro; Rojas, Graciela; Vöhringer, Paul A.; Fernández-Arcila, Mauricio; Luttges, Carolina; Irarrázaval, Matías; Bauer, Stephanie; Moessner, Markus (International journal of environmental research and public health, 2021)
The rapid internet penetration in Latin American countries has made it possible to implement digital mental health interventions. “Cuida tu Ánimo” (Take Care of Your Mood) is an internet-based program for the prevention and early intervention of depression in adolescents. A pilot study was conducted in Chile and Colombia to study the feasibility and acceptability of the program and estimate its effects. There were 199 participants (53.3% women; mean age = 14.8 years, SD = 1.0) recruited from two schools in Chile and two schools in Colombia. Qualitative and quantitative methods were applied for data collection and analyses. Although the levels of acceptance were moderate to high across all variables, adherence was lower than expected. The participants deemed important for an intervention of this type offered a higher level of interaction with team members through internet-based and face-to-face activities. Post-intervention outcomes show a reduction in depressive and anxious symptoms in adolescents in Chile, while there were no significant changes in the level of symptomatology in adolescents in Colombia. The women used the program more than the men. Results show the need to improve the intervention by increasing its levels of customization and developing strategies to achieve better adherence. The contradictory results of the program in Chile and Colombia suggest the importance of other variables beyond the content of the intervention, such as the setting or context of the intervention.